Checklist de morcegos (Mammalia: Chiroptera) das reservas de desenvolvimento sustentável Amanã e Mamirauá, estado do Amazonas: distribuição, morfologia e novos registros para o Brasil - NASCIMENTO, Andreza Cristina Soeiro do (2022)
Bats play several roles in the ecosystem and the Amazon is home to most of Brazil's bat diversity. The Sustainable Development Reserves (SDR) Amanã and Mamirauá, located in the state of Amazonas, are among the priority areas for biodiversity conservation due to their extremely high biological relevance. In this context, the aim of this study was to identify the species richness of bats in the SDR Mamirauá and Amanã in order to eliminate a taxonomic gap in the region and contribute to the knowledge of the chiropterofauna in the Amazon. A total of 274 specimens deposited in the mammal collection of the Museu Paraense Emílio Goeldi were analysed and identified in 4 families, 18 genera and 26 species. The most abundant species were Artibeus planirostris and Carollia perspicillata. Two geographic distribution extensions were identified, one of which was obtained from a species not sampled for more than 40 years.